Respiratory FimA-Specific Secretory IgA Antibodies Upregulated by DC-Targeting Nasal Double DNA Adjuvant Are Essential for Elimination of Porphyromonas gingivalis - Kataoka, Kosuke; Kawabata, Shigetada; Koyanagi, Kayo; Hashimoto, Yoshiya; Miyake, Tatsuro; Fujihashi, Kohtaro (Frontiers in Immunology, 2021)
Our previous studies showed that a combination of a DNA plasmid encoding Flt3 ligand (pFL) and CpG oligodeoxynucleotides 1826 (CpG ODN) (FL/CpG) as a nasal adjuvant provoked antigen-specific immune responses. In this study, we investigated the efficacy of a nasal vaccine consisting of FimA as the structural subunit of Porphyromonas gingivalis (P. gingivalis) fimbriae and FL/CpG for the induction of FimA-specific antibody (Ab) responses and their protective roles against nasal and lung infection by P. gingivalis, a keystone pathogen in the etiology of periodontal disease. C57BL/6 mice were nasally immunized with recombinant FimA (rFimA) plus FL/CpG three times at weekly intervals. As a control, mice were given nasal rFimA alone. Nasal washes (NWs) and bronchoalveolar lavage fluid (BALF) of mice given nasal rFimA plus FL/CpG resulted in increased levels of rFimA-specific secretory IgA (SIgA) and IgG Ab responses when compared with those in controls. Significantly increased numbers of CD8- or CD11b-expressing mature-type dendritic cells (DCs) were detected in the respiratory inductive and effector tissues of mice given rFimA plus FL/CpG. Additionally, significantly upregulated Th1/Th2-type cytokine responses by rFimA-stimulated CD4+ T cells were noted in the respiratory effector tissues. When mice were challenged with live P. gingivalis via the nasal route, mice immunized nasally with rFimA plus FL/CpG inhibited P. gingivalis colonization in the nasal cavities and lungs. In contrast, controls failed to show protection. Of interest, when IgA-deficient mice given nasal rFimA plus FL/CpG were challenged with nasal P. gingivalis, the inhibition of bacterial colonization in the respiratory tracts was not seen. Taken together, these results show that nasal FL/CpG effectively enhanced DCs and provided balanced Th1- and Th2-type cytokine response-mediated rFimA-specific IgA protective immunity in the respiratory tract against P. gingivalis. A nasal administration with rFimA and FL/CpG could be a candidate for potent mucosal vaccines for the elimination of inhaled P. gingivalis in periodontal patients.